Waiting as institution. Notes for an Institutional Analysis of Human Waiting Processes from a Discontinuous Materialism Perspective (Palimpsesto, 2023)
This essay proposes an alternative theory for analysing social and human waiting that breaks with the prevailing temporal approach. I suggest relocating waiting as a subject of study from the area of temporalities to that of social institutions. My approach draws on the theory of institutions offered by Discontinuous Materialism (DM) to analyse waiting processes. I argue that this perspective overcomes the gnoseological problems that current temporal theories of waiting have in the material field of these phenomena. The essay analyses the categories and concepts related to DM, such as Ï•-components and Ï€-totalities, anthropological space, and ceremony. It shows how they can be applied to waiting processes. This work also critiques two theoretical pillars on which current research is based: the idea that waiting is a fundamentally experiential and subjective phenomenon and the view that waiting constitutes ontologically negative (temporal) phenomena. The proposed institutional theory transforms waiting from a nebulous, liminal, and temporal phenomenon to one with materially visible and determinable contours. The essay concludes by demonstrating how the institutional character of waiting can further refine and delimit their specific field while also situating social and human waiting within a broad and diverse gnoseological field.
Keywords: Waiting Studies; Institution; Anthropological Space; Ceremony; Discontinuous Materialism